Pengaruh Pengelolaan BUMDes dan Pemberdayaan MAasyarakat terhadap Pertumbuhan Ekonomi Desa - Natoil, Heri; Linanjung, Yolanda Ardestya; Tamrin, Moh (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2025)
In this modern era, Village-Owned Enterprises (BUMDes) face complex challenges in their growth. This research sampled beneficiaries at BUMDes Gumregah Makmur Wirosari. The study results indicate that the BUMDes Management variable has a positive and significant influence on Village Economic Growth. The Community Empowerment variable positively and significantly influences Village Economic Growth. This research suggests that BUMDes Gumregah Makmur should improve its management by enhancing BUMDes performance. This will foster a positive perception among beneficiaries towards BUMDes Gumregah Makmur, as good management will lead to increased village economic growth.